Palliative prostatectomy of locally advanced and metastatic prostate cancer with obstructive uropathy (2018)
Conclusiones La pRTUP es una buena opción de tratamiento para la desobstrucción al tracto de salida de la vejiga secundaria al adenocarcinoma de próstata localmente avanzado, con mejoría considerable de los síntomas urinarios obstructivos bajos, el IPSS y con buena calidad de vida después de la intervención. Sin evidencia de progresión oncológica de la enfermedad secundaria a la intervención quirúrgica desobstructiva. Introduction Patients with locally advanced prostate cancer usually complaint of lower urinary tract symptoms secondary to bladder outlet obstruction as a consequence of obstructive uropathy due to prostate adenocarcinoma growth. The aim of this study is to evaluate QoL, IPSS, perioperative characteristics and safety of the palliative transurethral prostatectomy. Methods Retrospective study that asses 20 men with histopathological confirmed diagnosis of locally advanced prostate cancer and LUTS who underwent palliative prostatectomy. Results The average way of our simple was 73 years, alla of our patients underwent pTURP between 2011 and 2017, only one patient was discharged the same day of the procedure, the average internation time was 2.1 days, 5 patients (26%) had already underwent pTURP and needed a second time for palliation of the LUTS. Average initial IPSS was 23.2 5.4, the Qmax before the surgery was 8.3 1 and the majority of patients were classified as high risk according to D amico classification system due to the gleason score. Regards the QoL we found that in the physical and psychologic health domains the average score was low while in the other domains was considerably better. Postoperative IPSS was 16.5 3.4. Conclusion pTURP can be performed in patients with locally advanced prostate cancer and LUTS safely and effective with improvement in quality of life, micturition parameters and LUTS, without evidence that the surgical intervention increases oncologic progression of the disease. Copyright © 2018, Sociedad Colombiana de Urología.